2018
DOI: 10.2147/jpr.s172953
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Modic changes are related to axial symptoms after anterior cervical discectomy and fusion

Abstract: BackgroundThe objective of this study was to compare the clinical and radiological outcomes between patients with or without axial symptoms (AS) and investigate the risk factors associated with AS by multivariate regression analysis in anterior cervical discectomy and fusion (ACDF).Materials and methodsThe records of 117 patients who underwent ACDF were reviewed for clinical and radiological outcomes. These outcomes were evaluated before and after surgery and at the last follow-up. Preoperative Modic changes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…Based on their results, the authors proposed that endplate defects were the initiating factor that triggered a cascade of degradation that results in degenerative disc disease, which may precede the development of clinical symptoms. Although several studies have found that MC and endplate abnormalities may be related to axial neck pain, 15,16,20 as well as low back pain, 11,13,45 the present study found no association between any of the imaging groups and preoperative neck pain. These findings should be taken with special consideration as our control group had significant neck pain at baseline, which may have masked associations with pain and imaging phenotypes.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Based on their results, the authors proposed that endplate defects were the initiating factor that triggered a cascade of degradation that results in degenerative disc disease, which may precede the development of clinical symptoms. Although several studies have found that MC and endplate abnormalities may be related to axial neck pain, 15,16,20 as well as low back pain, 11,13,45 the present study found no association between any of the imaging groups and preoperative neck pain. These findings should be taken with special consideration as our control group had significant neck pain at baseline, which may have masked associations with pain and imaging phenotypes.…”
Section: Discussioncontrasting
confidence: 83%
“…10,11,13,14 Though there are limited studies addressing cervical MC, but there may also be an association with neck pain, and MC may indicate a more generalized debilitating state relative to patients without evidence of MC. [15][16][17] Structural endplate abnormalities (e.g., Schmorl's nodes) are localized endplate irregularities, which have also been linked to the development of low back pain 9 and in some instances precede disc degeneration. 18,19 Similar to MC, there is a paucity of studies that have addressed endplate abnormalities in the cervical spine.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cervical myelopathy patients may also complain of atypical symptoms, including vertigo, blurred vision, nausea, and hypomnesia 3,4 . For patients unresponsive to appropriate nonsurgical measures for at least 6 months, surgical treatment should be considered 5 . Primary aims of surgery are to relieve radiating arm pain in case of radiculopathy and to prevent progression of neurological deficit in case of myelopathy.…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, while some studies have found no association between MC and postoperative neck or arm pain, 14 others have found that the presence of MC may correlate with an increased likelihood of having these symptoms following ACDF. 13,15 Therefore, further clarification of the impact of MC on clinical and surgical outcomes is warranted in order to establish more realistic expectations following cervical spine surgery, particularly as patients with evidence of MC may be more likely to undergo 192 www.e-neurospine.org surgery than those that do not have MC. 16 Overall, little is known with respect to cervical MC and its various types, their topographical variations, and associations with pre-and postoperative symptoms/outcomes in patients undergoing an ACDF.…”
Section: Introductionmentioning
confidence: 99%